2014
DOI: 10.1186/1471-2407-14-422
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of patients with non-small cell lung cancer who underwent surgical resection following 4 lung cancer resection guidelines

Abstract: BackgroundTo compare survival of patients with non-small cell lung cancer (NSCLC) who underwent surgical resection and lymph node sampling based on guidelines proposed by the American College of Surgeons Oncology Group (ACOSOG), National Comprehensive Cancer Network (NCCN), the OSI Pharmaceutical RADIANT trial, and the International Association for the Study of Lung Cancer (IASLC).MethodsMedical records of patients with NSCLC who underwent surgical resection from 2001 to 2008 at our hospital were reviewed. Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 15 publications
(30 reference statements)
0
22
0
Order By: Relevance
“…As in the international literature, adenocarcinoma was the predominant histological type (61.8%) [12,16,17] , and males were in the majority (68.6%) [6,12] . Strong lines of evidence have shown that current smokers have a significantly higher risk of lung cancer than nonsmokers.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…As in the international literature, adenocarcinoma was the predominant histological type (61.8%) [12,16,17] , and males were in the majority (68.6%) [6,12] . Strong lines of evidence have shown that current smokers have a significantly higher risk of lung cancer than nonsmokers.…”
Section: Discussionmentioning
confidence: 82%
“…Surgery is a potentially curative treatment for earlystage NSCLC patients (stage I and II) [5,6] but, unfortunately, only 15-30% of the patients are eventually suitable for surgical resection with a curative intent [2,4] . Tumor recurrence is the most common cause of treatment failure after surgical resection [4,5,8,12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, variables, including increasing year, age >65 years, male sex, non-African American race, academic centers, lobectomy, and clinical T2 disease, have been shown to correlate with >15 nodes that were assessed. Furthermore, Yue et al reported that increased adherence to these guidelines was associated with improved survival (15).…”
Section: Current Guidelines For Adequate Nodal Assessmentmentioning
confidence: 99%
“…Non‐small cell lung carcinoma (NSCLC) accounts for 85% of all lung cancer where adenocarcinoma (AC) is the most common histology . The strongest prognostic factors of survival for patients with NSCLC are the TNM stage , advanced age, history of weight loss , ethnicity , and some genetic mutations (i.e., EGFR, K‐RAS, p53) .The three major NSCLC histological types; squamous cell carcinoma (SCC), AC, and large cell carcinoma (LCC) have also been shown to influence survival in some studies , but not in all . Bronchioloalveolar adenocarcinoma (BAC) that was described as a subtype of AC, has been thought to have a better prognosis than non‐BAC adenocarcinomas .…”
mentioning
confidence: 99%